2020
DOI: 10.1007/s12144-020-01193-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Pandemic Anxiety Scale (CPAS-11): development and initial validation

Abstract: The mental health impact of the COVID-19 pandemic will increase as the outbreak continues and persist even after the pandemic passes. We developed an 11-item Coronavirus Pandemic Anxiety Scale (CPAS-11) to measure symptoms of anxiety related to the COVID-19 pandemic to help identify individuals who might need mental health services. In developing the scale items, we considered previous research and theory on anxiety symptoms and symptoms reported by clinically referred cases in the Philippines. The scale was v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
0
17
0
2
Order By: Relevance
“…The SAVE-6 scale was extracted from the original SAVE-9 scale for measuring the behavior or thoughts of healthcare workers during the COVID-19 pandemic. Previous rating scales were developed to inquire about physiological arousal symptoms of individuals associated with clinically elevated fear and anxiety (the Coronavirus Anxiety Scale, Lee, 2020a); feelings of anxiety, nervousness, muscle tension, and behaviors of avoidance (the COVID-19-Anxiety Questionnaire, Petzold et al, 2020); worry, increased heartbeat, or repetitive thoughts (the Fear of COVID-19 scale, Ahorsu et al, 2020; the Coronavirus Pandemic Anxiety Scale, Bernardo et al, 2020; the COVID-19 Anxiety Scale, Silva et al, 2020); or behaviors of avoidance, checking, and worrying (the COVID-19 Anxiety Syndrome Scale, Nikcevic and Spada, 2020). The SAVE-9 scale consists of items inquiring about the apprehension of an individual during the current pandemic situation, work-related stress of healthcare workers, worry about avoidance behavior of others, and concern about their own health and the health of their family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAVE-6 scale was extracted from the original SAVE-9 scale for measuring the behavior or thoughts of healthcare workers during the COVID-19 pandemic. Previous rating scales were developed to inquire about physiological arousal symptoms of individuals associated with clinically elevated fear and anxiety (the Coronavirus Anxiety Scale, Lee, 2020a); feelings of anxiety, nervousness, muscle tension, and behaviors of avoidance (the COVID-19-Anxiety Questionnaire, Petzold et al, 2020); worry, increased heartbeat, or repetitive thoughts (the Fear of COVID-19 scale, Ahorsu et al, 2020; the Coronavirus Pandemic Anxiety Scale, Bernardo et al, 2020; the COVID-19 Anxiety Scale, Silva et al, 2020); or behaviors of avoidance, checking, and worrying (the COVID-19 Anxiety Syndrome Scale, Nikcevic and Spada, 2020). The SAVE-9 scale consists of items inquiring about the apprehension of an individual during the current pandemic situation, work-related stress of healthcare workers, worry about avoidance behavior of others, and concern about their own health and the health of their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Several rating scales were developed and applied in 2020 in response to the pandemic: the five-item Coronavirus Anxiety Scale developed by Lee (2020a), the COVID-19-Anxiety Questionnaire modified by Petzold et al (2020) based on the DSM-5 Severity Measure for Specific Phobia-Adult Scale, the seven-item Fear of COVID-19 Scale developed by Ahorsu et al (2020), the four-item Obsession with COVID-19 Scale developed by Lee (2020b), the 11-item Coronavirus Pandemic Anxiety Scale developed by Bernardo et al (2020), the two-factor nine-item COVID-19 Anxiety Syndrome Scale (six items for perseverance and three items for avoidance) developed by Nikcevic and Spada (2020), and the seven-item COVID-19 Anxiety Scale developed by Silva et al (2020). These scales inquired about the anxiety of, repetitive thoughts of, or anxietyrelated physiological arousal symptoms in an individual.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the SAVE-9 scale was clustered into two factors: factor I—“anxiety about the viral epidemic” and factor II—“work-related stress associated with the viral epidemic.” We previously explored the validity of factor I (namely, SAVE-6) for measuring anxiety of the general population in Korea ( 8 ) and Lebanon ( 9 ). Several rating scales such as Coronavirus Anxiety Scale (CAS) ( 10 ), COVID-19-Anxiety Questionnaire ( 11 ), Fear of COVID-19 Scale ( 12 ), Obsession with COVID-19 Scale ( 13 ), Coronavirus Pandemic Anxiety Scale ( 14 ), COVID-19 Anxiety Syndrome Scale ( 15 ), and COVID-19 Anxiety Scale ( 16 ) were also developed and applied to assess the anxiety response of the general population to the viral epidemic. SAVE-6 included items inquiring about the apprehension of an individual during the current pandemic situation, worry about avoidance behavior of others, and concern about their own health and that of their family members ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the symptoms of anxiety manifested by individuals during the epidemic/pandemic may be similar to those expressed in other anxiety situations, it is noticed that there are specific forms of anxiety-related distress responses during viral outbreaks and the COVID-19 pandemic as well (Asmundson and Taylor, 2020 ). Some major factors which contribute to specificity of pandemic anxiety are the fear of becoming infected and dying, socially disruptive behaviors, and adaptive behaviors (Asmundson and Taylor, 2020 ; Bernardo et al, 2020 ; Wang et al, 2020 ). In other words, the increased risk of death (Aldridge et al, 2020 ), additionally unemployment and economic losses (Coibion et al, 2020 ), and numerous restrictions introduced by the countries' governments around the world, lead to negative health consequences (Meyerowitz-Katz et al, 2021 ), that include pandemic anxiety with its specifics as well (Bernardo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some major factors which contribute to specificity of pandemic anxiety are the fear of becoming infected and dying, socially disruptive behaviors, and adaptive behaviors (Asmundson and Taylor, 2020 ; Bernardo et al, 2020 ; Wang et al, 2020 ). In other words, the increased risk of death (Aldridge et al, 2020 ), additionally unemployment and economic losses (Coibion et al, 2020 ), and numerous restrictions introduced by the countries' governments around the world, lead to negative health consequences (Meyerowitz-Katz et al, 2021 ), that include pandemic anxiety with its specifics as well (Bernardo et al, 2020 ). Accordingly, a fair number of studies have been published indicating an increase in anxiety symptoms in pregnant women during the COVID-19 pandemic (Ayaz et al, 2020 ; Corbett et al, 2020 ; Durankuş and Aksu, 2020 ; Kotabagi et al, 2020 ; Lebel et al, 2020 ; Moyer et al, 2020 ; Saccone et al, 2020 ; Wu et al, 2020 ; Yue et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%